2005
DOI: 10.1080/13550280590952817
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors induce reactivation of herpes simplex virus type 1 in a latency-associated transcript–independent manner in neuronal cells

Abstract: Histone acetylation is implicated in the regulation of herpes simplex virus type 1 (HSV-1) latency. However, the role of histone acetylation in HSV-1 reactivation is less clear. In this study, the well established model system, quiescently-infected, neuronally-differentiated PC12 (QIF-PC12) cells, was used to address the participation of histone acetylation in HSV-1 reactivation. In this model, sodium butyrate and trichostatin A (TSA), two histone deacetylase inhibitors, stimulated production of infectious HSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 61 publications
(59 reference statements)
7
74
2
Order By: Relevance
“…This conclusion is reinforced by the observation that CTB, a drug that binds to p300/CBP and activates it by altering its conformation effectively, induced viral gene expression in ganglia incubated in medium containing NGF and EGF without prior or concurrent protein synthesis. iv) Studies reported elsewhere have shown that wide-spectrum HDAC inhibitor induced HSV reactivation (25). In this study we reaffirm the expectation that neurons harboring latent virus by inhibition of the HDACs do not require prior or concurrent protein synthesis.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This conclusion is reinforced by the observation that CTB, a drug that binds to p300/CBP and activates it by altering its conformation effectively, induced viral gene expression in ganglia incubated in medium containing NGF and EGF without prior or concurrent protein synthesis. iv) Studies reported elsewhere have shown that wide-spectrum HDAC inhibitor induced HSV reactivation (25). In this study we reaffirm the expectation that neurons harboring latent virus by inhibition of the HDACs do not require prior or concurrent protein synthesis.…”
Section: Discussionsupporting
confidence: 77%
“…Earlier studies have shown that HSV-1 can be reactivated from latently infected neurons by histone deacetylase (HDAC) inhibitors (25). The purpose of these studies was to verify that HDAC inhibitors, both broad spectrum and those with some degree of specificity, reactivate HSV-1 in latently infected TG maintained in organ culture incubated in medium containing NGF + EGF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that in this experiment, three of the mice inoculated with R112 succumbed to infection between days 9 and 14. that fails to repress the genome in nonneuronal cells. Consistent with this hypothesis are reports that virus reactivation from latent state is enhanced by HDAC inhibitors (15)(16)(17). To test the hypothesis, we inserted a gene encoding REST devoid of both Nand C-terminal repressor domains into the wild-type HSV-1 genome.…”
Section: Discussionmentioning
confidence: 72%